Management of Zakat, Infaq, and Shadaqah (ZIS) Funds in Driving Poverty Alleviation to Achieve Sustainable Development Goals (SDGs): A Case Study of BAZNAS Kediri City - Khoiri, Ahmad (Journal of Development Research, 2024)
Quality management of Zakat, Infaq, and Shadaqah (ZIS) funds is essential for alleviating poverty in Kediri City, where the number of poor residents reached 21,030 in 2023. ZIS distribution programs must align with the Sustainable Development Goals (SDGs) to support the government's efforts toward sustainable development. This research uses a case study approach at BAZNAS Kediri City. Data were collected through participatory observation, in-depth interviews with leaders, staff, and beneficiaries, and document analysis related to ZIS fund management for poverty alleviation and SDG implementation. Qualitative data analysis was conducted to gain insights into management practices at BAZNAS Kediri. The findings indicate that ZIS fund management at BAZNAS begins with planning through the Annual Work Plan and Budget (RKAT). In 2023, the total distribution reached IDR 2,553,245,369, benefiting 7,292 individuals. This accounts for 34.67% of the poor population in Kediri, with 4 beneficiaries lifted out of poverty through productive business capital assistance. However, BAZNAS’s distribution is mainly consumptive due to insufficient oversight of productive assistance. Additionally, BAZNAS reports its activities periodically for accountability. BAZNAS Kediri has integrated its programs with the SDGs, although three goals clean and affordable energy, marine ecosystems, and terrestrial ecosystems remain unrealized. This is due to prioritizing ZIS fund distribution for programs that enhance the economy, education, health, and outreach. Furthermore, there is a lack of detailed planning regarding the SDGs in the RKAT.